2017
DOI: 10.18203/issn.2454-5929.ijohns20175618
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice about allergic rhinitis in a rural population, Kancheepuram district, Tamil Nadu

Abstract: INTRODUCTIONAllergic rhinitis is hypersensitivity of the nasal mucosa to allergens. It can be associated with hypersensitivity of the lower airways, atopic dermatitis and allergic conjunctivitis. Allergic rhinitis is becoming more common but still an underreported and under treated condition. The prevalence of allergic rhinitis is increasing with time. The worldwide prevalence of allergic rhinitis is about 10-30% in adults.1 Allergic rhinitis is a global health problem affecting social life, sleep, school and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 3 publications
(4 reference statements)
5
5
1
1
Order By: Relevance
“…The KAP of patients with AR in Saudi Arabia was reported to be low [ 12 , 14 ]. Similar results were reported in India [ 13 ] and four Southeast Asian nations [ 15 ]. Thai patients have poor knowledge of the risks of immunotherapy for AR [ 20 ], and similar results were observed in German athletes with AR [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The KAP of patients with AR in Saudi Arabia was reported to be low [ 12 , 14 ]. Similar results were reported in India [ 13 ] and four Southeast Asian nations [ 15 ]. Thai patients have poor knowledge of the risks of immunotherapy for AR [ 20 ], and similar results were observed in German athletes with AR [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…A study in Saudi Arabia showed poor KAP of patients with AR toward intranasal corticosteroids [ 12 ]. Similar results were observed in rural India [ 13 ] and Southeast Asian nations [ 15 ]. The KAP of Chinese patients with AR on AR is poorly known.…”
Section: Introductionsupporting
confidence: 87%
“…Contrary to the previous studies, most of the individuals in the present study had adequate knowledge of AR [5,16]. In this perspective, comparison between different studies is impractical because of the various instruments used to assess knowledge.…”
Section: Discussioncontrasting
confidence: 62%
“…Pengetahuan, sikap dan praktik yang membentuk perilaku kesehatan berperan penting dalam menentukan risiko terjadinya rhinitis alergi. Penelitian di Arab Saudi dan India menunjukkan bahwa pengetahuan yang kurang terkait dengan rhinitis alergi mengakibatkan sikap dan praktik yang buruk terhadap rinitis alergi (Alreshidi et al, 2017;Rajasekaran & Ghosh, 2018). Penelitian Purba et al (2013) menunjukkan bahwa perilaku terhadap TDR mempengaruhi kepadatan pop-ulasi TDR dan Wang et al (2014) di Wuhan juga melaporkan tingginya alergen TDR di dalam rumah berhubungan dengan beratnya gejala rhinitis alergi.…”
Section: Pendahuluanunclassified